Rancang Bangun Sistem Informasi Penjualan Ukiran Tembaga di Daerah Boyolali Berbasis Web - , Heri, Drs. Sujalwo, M.Kom (2017)
Website engraving copper provides convenience to the buyer to make a reservation or purchase engraving copper craft other than that the website is also easier for the craftsman or supplier to sell crafts they have and with this website sales process engraving copper will run more easily and quickly and the results of sales transactions else is stored into the database, before this website craftsmen carving copper in the area Cepogo Boyolali in sales are still using email or come directly to the gallery of craftsmen and sales transaction still manually recorded into the book, the process that this manual is felt craftsmen less efian and will hamper sales of copper engraving thus hence made this website to help craftsmen in advancing productivity. Making this website using programming language PHP, MySQL and user interface using HTML, CSS and use the Google Chcome and Xampp. The website system in the test by conducting a questionnaire to the buyer or user. Results of the questionnaire showed buyers with this website can help the sales activities especially in the ease to access the website for the interpretation percentage reached 82.5% was the highest percentage, whereas in the case of the publication of the website to get the lowest percentage of interpretation that is 57.5%.